Answer:
A) x = − 1, y = 2, z = 3
Explanation:
4x − 2y + 3z = 1
x + 3y − 4z = −7
3x + y +2z = 5
Lets eliminate x by multiplying the second equation by -4
4x − 2y + 3z = 1
-4x - 12y + 16z = 28
-----------------------------
-14y +19z = 29
Lets eliminate x by multiplying the second equation by -3
-3x + -9y +12z = 21
3x + y +2z = 5
---------------------------
-8y +14z =26
We now have 2 equations and 2 unknowns
-14y +19z = 29
-8y +14z = 26 Divide this by 2 = -4y +7z = 13
Multiplying the first equation by 4 and the second by -14
-56y +76z =116
56y -98z = -182
----------------------------
-22z =-66
Divide each side by -22
-22z/-22 = -66/-22
z=3
Now we need to find y
-14y +19z = 29
-14y +19(3) =29
-14y+ 57 = 29
-14y =29-57
-14y =-28
y =2
Now we need to find x
x + 3y − 4z = −7
x + 3(2) -4(3) =-7
x+6 -12 =-7
x-6 = -7
x = -1